Factors associated with intelligence in young children with Down syndrome - Frieda Handayani Kawanto; Soedjatmiko Soedjatmiko; Aryono Hendarto (Indonesian Pediatric Society Publishing House, 2012)
Introduction Despite the considerable number of children with Do\Vll syndrome in Indonesia, there is little data available on the success of intervention programs. This study was performed to define factors affecting the intelligence of young children with Do\Vll syndrome. Objective To determine factors associated Mth lower intelligence in children with Down syndrome, including growth parameters and participation in intervention programs. Methods This cross􀁃sectional study was undertaken from December 2010 to March 2011. Subjects were 60 children with Down syndrome aged 2􀁃6 years who were enrolled in an intervention program at both the Medical Rehabilitation Department, Cipto Mangunkusumo Hospital, and the Growth and Development Clinic, Harapan Kita Women's and Children's Hospital. Parents' data was obtained through self history􀁃taking and perusal of medical records. Subjects' anthropometric data (body weight, body height, and head circumference) was obtained through measurements using calibrated instruments. A psychologist administered IQ tests on the subjects. Results of the anthropometric and IQ tests were given to parents one week following the examinations. Results From the 111 children with Down syndrome registered in the intervention programs, 60 children (36 boys and 24 girls) met the inclusion criteria. The mean age of subjects was 4 years 6 months. Most subjects were well􀁃 nourished. Fifty􀁃five subjects had microcephaly. Eighty􀁃two percent of subjects participated in the program regularly and 70% of subjects had started in the program at less than 1 year of age. Subjects' mean IQ was 52.8. Analysis showed that girls, subjects who were overweight and obese, subjects with microcephaly, those with irregular attendance in the program, and those living under the poverty line were at highest risk for severe mental retardation. Conclusion Factors associated v.ith the intelligence in children with Down syndrome were female gender, overweight/obesity,  severe microcephaly, below􀁃poverty line economic status, and irregular participation in the program. [Paediatr Indones. 2012;52:194-9].